EVGE 2011 NOMINATION - Mouzouropoulos, Theseas (My University, 2026)
The award was received by the Greek Graphic Design & Illustration Awards for the exemplary design and concept in the category Logo Design. The logo was designed professionally for a local company
Keywords: Arts and entertainment